Estimator-based single phase second order variable structure controller for the pitch control of a variable speed wind turbine - Nguyen, Cong-Trang; Phan, Tai Thanh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
A novel single phase second order variable structure controller (SPSOVSC) based on estimated variables and output information only is presented for the variable speed wind turbine (VSWT) system. In contrast with a recent method, the output feedback and second order sliding mode control techniques are deliberated for the SPSOVSC design in the VSWT. The selection of an integral single-phase sliding surface is established such that the reaching phase required in the basic variable structure control (BVSC) scheme is removed since the plant’s state trajectories always begin from the sliding surface. In addition, appropriate stability constraints by Lyapunov based novel linear matrix inequality (LMI) technique are acquired to guarantee the entire VSWT plant’s steadiness. Using the proposed techniques, the SPSOVSC is developed to modify BVSC to advance the performance of VSWT plant in terms of overshoot and settling time. The results show the new scheme is highly robust in sliding variable's fast convergence to zero asymptotically. It is obvious that the robustness of the proposed controller in terms of steadiness and usefulness of the scheme.